Ebolaviruses: New roles for old proteins - Cantoni, Diego; Rossman, Jeremy S. (PLOS Neglected Tropical Diseases, 2018)
Author summary Between 2014 and 2016, West Africa experienced the largest Ebolavirus outbreak in recorded history. The international containment effort spurred extensive research that is enhancing our understanding of ebolavirus replication and pathogenicity. Much has been learned about the main function of each ebolavirus protein since the discovery of the virus in 1976; however, recent ebolavirus research has led to the discovery of many new protein functions. These newly discovered roles are revealing new mechanisms of virus replication and pathogenesis and increasing our understanding of how each component of the virus works. This review highlights the newly discovered roles of ebolavirus proteins in order to provide a more encompassing view of ebolavirus replication and pathogenicity.